2021
DOI: 10.1155/2021/6649362
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Element Analysis in Some Seafood in the Coastal Zone of the Red River (Ba Lat Estuary, Vietnam) by Green Sample Preparation and Inductively Coupled Plasma-Mass Spectrometry (ICP-MS)

Abstract: Fisheries and aquaculture production in the coastal zone of Vietnam contribute significantly to the national economy. However, seafood quality and safety, especially in terms of metal contents, are of increasing concern, for both domestic and international markets. This paper presents the results of an investigation in some trace metal elements (iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), arsenic (As), cadmium (Cd), and mercury (Hg)) concentrations in some fishes, crustaceans, and molluscs in the coasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A significant impact of marine coastal pollution is metal-contaminated seafood, which has raised public attention due to its potential risks to human health [ 2 ]. Studies of PTMs in seafood have been increasing in the literature since the biomonitoring data are related to the human health risks of metal toxicity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In particular, many such biomonitoring studies with health risk assessments were reported from Pakistan [ 1 ], Thailand [ 2 ], Brazil [ 3 ], Serbia [ 4 ], China [ 5 , 19 , 21 , 24 ], Nigeria [ 6 , 25 ], Kuwait [ 8 ], Malaysia [ 9 , 26 ], Vietnam [ 11 ], Bosnia and Herzegovina [ 12 ], Romania [ 15 ], Serbia [ 16 ], Hungary [ 20 ] and Turkey [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A significant impact of marine coastal pollution is metal-contaminated seafood, which has raised public attention due to its potential risks to human health [ 2 ]. Studies of PTMs in seafood have been increasing in the literature since the biomonitoring data are related to the human health risks of metal toxicity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In particular, many such biomonitoring studies with health risk assessments were reported from Pakistan [ 1 ], Thailand [ 2 ], Brazil [ 3 ], Serbia [ 4 ], China [ 5 , 19 , 21 , 24 ], Nigeria [ 6 , 25 ], Kuwait [ 8 ], Malaysia [ 9 , 26 ], Vietnam [ 11 ], Bosnia and Herzegovina [ 12 ], Romania [ 15 ], Serbia [ 16 ], Hungary [ 20 ] and Turkey [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of PTMs in seafood have been increasing in the literature since the biomonitoring data are related to the human health risks of metal toxicity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In particular, many such biomonitoring studies with health risk assessments were reported from Pakistan [ 1 ], Thailand [ 2 ], Brazil [ 3 ], Serbia [ 4 ], China [ 5 , 19 , 21 , 24 ], Nigeria [ 6 , 25 ], Kuwait [ 8 ], Malaysia [ 9 , 26 ], Vietnam [ 11 ], Bosnia and Herzegovina [ 12 ], Romania [ 15 ], Serbia [ 16 ], Hungary [ 20 ] and Turkey [ 22 ]. The six PTMs that were investigated in the present study were Cd, Cu, Fe, Ni, Pb and Zn because they are common anthropogenic metals and could potentially cause human health risks [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ,…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, monitoring water quality is very important to evaluate water conditions. Some of the most recent analytical methods commonly used to detect heavy metal ions are inductively coupled plasma-optical emission spectroscopy (ICP-OES) [3], inductively coupled plasma mass spectrometry (ICP-MS) [4], atomic absorption spectrometer (AAS) [5], cyclic voltammetry [6], graphite furnace atomic absorption spectrometer (GFAAS) [7] and X-ray fluorescence spectrometry [8]. The advantages of using these methods are that they have relatively wide application, high sensitivity, high selectivity, and can be used to measure a relatively large number of elements.…”
Section: ■ Introductionmentioning
confidence: 99%